2015
DOI: 10.1063/1.4921808
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric polarization and defect-dipole switching in an epitaxial (111) BiFeO3 thin film

Abstract: Articles you may be interested inChemical solution deposition derived (001)-oriented epitaxial BiFeO3 thin films with robust ferroelectric properties using stoichiometric precursors (invited)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…An important mechanism that has not been considered in previous studies is the effect of defect dipoles, which have been widely observed in oxide perovskites. The formation of native defects, e.g., iodide vacancy, will leave behind a defect dipole in the PbI 6 or SnI 6 octahedron due to an offset of the positive and negative charge centers (Figure a). Defect dipoles can exist in bulk perovskite lattice or on its free surface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…An important mechanism that has not been considered in previous studies is the effect of defect dipoles, which have been widely observed in oxide perovskites. The formation of native defects, e.g., iodide vacancy, will leave behind a defect dipole in the PbI 6 or SnI 6 octahedron due to an offset of the positive and negative charge centers (Figure a). Defect dipoles can exist in bulk perovskite lattice or on its free surface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The sub-surface charge can be associated with accumulation of charged defects near the surface [12,59] and/or alignment of defect dipoles under the intrinsic domain depolarizing field. [6,60,61] The existence of the mobile charge defects in BFO is well-known, while details of the defect chemistry are still under discussion, [8,62,63] because the defect composition is very sensitive to the atmosphere and sample preparation conditions. [62,64,65] The defect chemistry model assumes formation of different point defects in the bismuth ferrite, namely: oxygen and bismuth vacancies (see details in Section 4, Supporting Information).…”
Section: Structural and Chemical Characterizationmentioning
confidence: 99%
“…Based on the above chemical analysis of the surface, it can be proposed that the downward polarization can be screened by holes and positively charged oxygen vacancies ( ) O •• V , while negatively charged iron (V′′′ Fe ) and bismuth vacancies (V′′′ Bi ) participate in screening of the upward polarization (Figure 7a). Though the depolarization field can be partially reduced by the defect complexes with a dipole moment (defect dipoles), [6,60,61] their impact on the reduction of the depolarization field is seen to be minor because they have high activation energies for transport compared to the single charged defects. [63] The contribution of the charged defects to the dynamics of the polarization switching is dependent on the defect mobility.…”
Section: Monitoring Dynamics Of Charged Defects and Their Contributio...mentioning
confidence: 99%
“…In theory this should also hold for ferroelectric superlattices that have compositional inversion symmetry [2][3][4]. However, in practice, electric polarization asymmetry, where one polarization state is preferred over another, or in other words, a built-in bias, is often seen in ferroelectric thin films and superlattices [5][6][7][8][9]. Many contributing factors have been suggested as sources of polarization asymmetry.…”
Section: Introductionmentioning
confidence: 99%